PENGALOKASIAN WAKTU BELAJAR MAHASISWA DI BAGIAN KLINIK SELAMA PROGRAM PENDIDIKAN DOKTER TAHAP PROFESI DI FK UGM - , CANDRIKA DINI KHAIRANI, dr. Yoyo Suhoyo, M.Med.ED. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
contrast with the less structured clinical years. The following years are centered on clinical experience and less uniform especially between departments. This variation in clinical education is anongoing problem in medical education. An understanding of student time allocation is very important to determine whether the students are experiencing clinical education the way the faculty intended. Objective: To assess student time allocation during clinical rotation in Faculty of Medicine, University of Gadjah Mada. Subject:209 Students who have undergone clinical rotation in Faculty of Medicine, University of Gadjah Mada from 11 departments, Method:This is a descriptive study using quantitative and cross sectional design. The students in Faculty of Medicine University Gadjah Mada who have undergone clinical rotation completed a questionnaire that recorded the time they spent on eight clerkship activities over 2 weeks. Result:The students spent about 7 hourse a day on clerkship activities. Most time was spent on structurally organized education (20,09%), followed by observing instructor (15,97%) and self-study(15,15%). Less time was available for clinical meetings, independent hospital activities and directly supervised activities. There was a variety in distribution of time use in different departments. There was a significant difference of the unproductive time allocation between students from year 2007 and non 2007. Conclusion:Across departments, students in Faculty of Medicine Gadjah Mada University spent wide variety of time allocations. The time allocation were dominated by structured activities. There were little time allocated for supervised patient interaction and considerable time allocated for observing instructor and self-study indicated less time allocated for supervision and direct interaction with patient.